2021
DOI: 10.3892/ijo.2021.5229
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 blockade sensitizes osteosarcoma to doxorubicin by inducing autophagic cell death via PI3K‑Akt‑mTOR pathway inhibition

Abstract: Doxorubicin is one of the most frequently used chemotherapy drugs in the treatment of osteosarcoma (OS), but the emergence of chemoresistance often leads to treatment failure. C-X-C motif chemokine receptor 4 (CXCR4) has been demonstrated to regulate OS progression and metastasis. However, whether CXCR4 is also involved in OS chemoresistance and its molecular mechanisms has yet to be fully elucidated. In the present study, CXCR4-mediated autophagy for OS chemotherapy was investigated by western blot analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Activation of the Akt/mTOR has been reportedly linked to the oncogenic events mediated by CXCR4 14,15 . The expression of CXCR4 and AKT/mTOR pathway‐related proteins were detected by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the Akt/mTOR has been reportedly linked to the oncogenic events mediated by CXCR4 14,15 . The expression of CXCR4 and AKT/mTOR pathway‐related proteins were detected by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…97 More importantly, a recent study of Liao et al pointed out that CXCR4 blocker increased DOX sensitivity of OS through activating autophagic cell death by negatively regulating PI3K/ AKT/mTOR signaling pathway. 98 We conclude from above that mild autophagy could increase chemoresistance because of cytoprotective effect, whereas excessive autophagy reverses chemoresistance through activating cell death (Table 1). Thus, our study has important guiding significance in developing autophagy inhibitors or autophagy activators to modulate chemoresistance of OS in the future.…”
Section: Autophagy and Os Chemotherapymentioning
confidence: 87%
“…Similarly, as an autophagy inducer, voacamine could enhance the chemosensitivity of DOX‐resistant U2OS cells through activating autophagic cell death 97 . More importantly, a recent study of Liao et al pointed out that CXCR4 blocker increased DOX sensitivity of OS through activating autophagic cell death by negatively regulating PI3K/AKT/mTOR signaling pathway 98 …”
Section: The Role Of Autophagy In Osmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT/mTOR signaling also participates in GEM resistance of PC cells by regulating the Warburg effect (Cui et al 2021 ). Moreover, PI3K/AKT/mTOR signaling is reported to be the downstream signaling pathway after the activation of CXCR4 (Yi et al 2019 ; Yi and Gao 2019 ; Liao et al 2021 ). In this study, we found that CXCL12 secreted by PSCs could bind to CXCR4 and then activate PI3K/AKT/mTOR signaling in PC cells.…”
Section: Discussionmentioning
confidence: 99%